2017
DOI: 10.1002/cncr.31152
|View full text |Cite
|
Sign up to set email alerts
|

Variants with a low allele frequency detected in genomic DNA affect the accuracy of mutation detection in cell‐free DNA by next‐generation sequencing

Abstract: Because only a small fraction of total cfDNA might be derived from tumor cells, only mutations with the first allele frequency pattern may be regarded as tumor-specific mutations in cfDNA. Effective filtering of background mutations will be required to improve the accuracy of mutation calls in cfDNA. Cancer 2018;124:1061-9. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Nevertheless, important issues focusing on which subclones derived from LAM cells give rise to metastasis and the potential clinical benefits remain to be addressed. In our study, mutation levels in cfDNA from LAM patients were more than those from normal individuals, which was compatible with previous published studies that circulating cfDNA levels from nonapoptotic DNA fragments are drastically elevated in cancer patients . However, it should be noted that the displayed mutational burden was calculated based on predicted genetic mutations due to limited targeted genes in our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, important issues focusing on which subclones derived from LAM cells give rise to metastasis and the potential clinical benefits remain to be addressed. In our study, mutation levels in cfDNA from LAM patients were more than those from normal individuals, which was compatible with previous published studies that circulating cfDNA levels from nonapoptotic DNA fragments are drastically elevated in cancer patients . However, it should be noted that the displayed mutational burden was calculated based on predicted genetic mutations due to limited targeted genes in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Fragments of circulating cfDNA were shown to be derived from apoptosis, necrosis or active secretion, which can be detected in the cell-free components of plasma and serum. 29 The mutant allele frequencies in cfDNA from apoptotic cells were almost identical with those in the blood cells. 29,30 Consistent with this, we observed that mutant allele frequencies in cfDNA were distinct from gDNA, and that had a significant correlation with gDNA in coexisting mutations.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations